Democracy and Resource Rents. - Collier, P; Hoeffler, A (GPRG, 2005)
The phenomenon of the resource-rich developing country is once again of global importance. Reversing a trend, the number of such countries has sharply increased due to a wave of resource discoveries, the break-up of the USSR, and the rise in commodity prices. It is now conventional that resource rents have usually reduced growth. The explanation has shifted from the purely economic 'Dutch disease' to political economy: rents both undermine governance, and are dysfunctional in the context of poor governance. This shift in explanation is important because the new resource boom is occurring against a backdrop of democratization. During the resource boom of the 1970s, the average resource-rich country scored only 0.96 on the Polity IV scale of political rights (the scale ranges 0-10). By the mid-1990s the score had risen to 3.47.1 American policy following the intervention in Iraq is explicitly to democratize the Middle East, the world's most important resource-rich region. The purpose of this paper is to investigate, theoretically and empirically, how democracy and natural resource rents are likely to interact. Our analysis contributes to the active literature on the relationship between geography, institutions, and growth.